CEO Inside Debt and Risk Taking: Evidence From Property–Liability Insurance Firms. Issue 2 (21st July 2017) - Milidonis, Andreas; Nishikawa, Takeshi; Shim, Jeungbo
Abstract: We examine the incentive effects of CEO inside debt holdings (pensions and deferred compensation) on risk taking using the sample of U.S. publicly traded property–liability insurers. To represent managerial risk taking, we employ value at risk (VaR) and expected shortfall (ES), which capture extreme movements in the lower tail of insurer stock return distribution. We also estimate firm default risk, equity volatilities, and insurance‐related risk as alternative measures of risk taking. We document that inside debt represents a significant component of CEOs' compensation in the insurance industry. We find that there is a significant and negative relationship between CEO inside debt holdings and risk‐taking behavior. The results suggest that the structure of executive debt‐like compensation could be a potential method of reducing managers' risk‐taking incentives.